Recent trends in solar PV inverter topologies. (1st May 2019) - Dogga, Raveendhra; Pathak, M.K.
Abstract: The choice of the right type of power converters to meet the different requirements for any application has a great influence on the optimum performance, especially in Solar Photovoltaic (PV) systems. In the last two decades, enormous developments have been taking place in PV systems in power electronics domain to meet the utility/load requirements from the low voltage, non-linear, and highly sensitive (to environmental conditions) power source (solar PV module/array). In particular, many inverter topologies have been introduced to incorporate the several unique features to fulfil PV system requirements, such as (a) intrinsic boost capabilities, (b) isolation, (c) high efficiency, (d) good power decoupling, (e) dual grounding function, (f) single stage solar power conversion capabilities, (g) compact design and (h) good power quality, for both stand-alone and grid-connected applications. Since, inverter is an essential part in PV systems, a large number of research publications have been published with new topologies/modifications, which leads to this persuasion of a critical review. In this manuscript, a detailed analysis and classification about all the inverter attributes are presented for the 45 reviewed topologies, intended to serve as an expedient reference for selecting best power converter for a specific requirement in PV systems.